(untitled) (Bangladesh Journal of Zoology, 2017)
Investigation on gastrointestinal helminths was conducted on 20 domestic fowl, 20 white leghorn, 20 layer and 20 cock of Dhaka city. Six species of helminth belonging to trematode, cestode and nematode were found to infect the different parts of alimentary canal of domestic fowl. The prevalence of helminths in domestic fowl were as follows: Catatropis verrucosa (25%), Amoebotaenia sphenoides (10%), Hymenolepis cantaniana (35%), Rallietina echinobothrida (55%), Ascardia galli (70%) and Heterakis gallinarum (30%) whereas, in white leghorn the prevalence of Rallietina echinobothrida (20%) and Ascardia galli (35%) were recorded. In layer, higher prevalence of Rallietina echinobothrida (55%) and Ascardia galli (60%) were recorded; in cock the prevalence of specific helminthes were as follows: Hymenolepis cantaniana (10%), Rallietina echinobothrida (40%), Cotugnia digonopora (20%), Ascardia galli (60%) and Heterakis gallinarum (25%). Along with the prevalence and intensity of infestation of different species of parasites, intensity were also recorded. Highest number of parasites were collected from intestine. Bangladesh J. Zool. 44(2): 245-254, 2016